Motivators and Barriers to Health Behaviors in African American Women - (:unkn) unknown (My University, 2018)
Women who identify as African American are at particularly high risk of developing obesity and associated health concerns such as diabetes, heart disease, and cancers. Eating healthfully and engaging in a minimal amount of physical activity are known to be both preventative and curative. Based on review of research, this study investigated potential constructs of Motivators and Barriers to health-supporting behaviors as they are perceived in African American women. The study also constructed a novel scale, Motivators and Barriers to Health Behaviors (MBHB), which intended to capture some constructs of each domain via two surveys. Also of interest was if composite scores of Motivators and/or Barriers factors may be able to predict Body Mass Index (BMI) or Waist Circumference (WC) measurements. Lastly, the study intended to gain insight into the types of beverages and foods that African American women preferred, as well as what grocery stores and fast food restaurants they frequent, and what types of physical activity they engaged in regularly. One hundred and twenty-six adult women identifying as African American and residing in the city of Milwaukee, Wisconsin participated in this investigation. Results from an Exploratory Factor Analysis (EFA) indicated five Motivators factors resulting from 21 items. They represented thematic constructs of Personal Health, Beverage and Food Preferences, Church and Spirituality, and Social Support, and one unanticipated factor labeled Physician Input. Results from a second EFA indicated four Barriers factors resulting from 16 items. They represented thematic constructs of Food Choices, Beverage Choices, Knowledge, and Family and Social Support. In addressing hypotheses of the study, Multiple Linear Regression (MLR) analyses were conducted. Results demonstrated that Motivators factors significantly predicted BMI and WC. Barriers items did not significantly predict neither BMI nor WC. Descriptive statistics demonstrating the outcome of open-ended questions of food and beverage preference, grocery story and fast food patronage, and physical activity were compiled. Results indicated that sodas were the most frequently cited as a preferred favorite beverage, followed by water. Drinks containing relatively high levels of sugar were cited at a ratio of three-to-one compared to water. Chicken was the most frequently cited preferred food; Pick-N-Save was the most frequented grocery store, and McDonald’s the most frequently cited fast food establishment. Finally, the physical activity cited most often was walking. Discussion of findings and implications for future research are addressed.
Keywords: African American Women; Community Culture; Exploratory; Food Preferences; Health Behaviors; Obesity